FC034: Genomic Approach of the Undetermined Kidney Disease. (3rd May 2022) - Robert, Thomas; Dussol, Bertrand; Jourde-Chiche, Noemie; Legris, Tristan; Moal, Valérie; Sallee, Marion; Pelletier, Marion; Raymond, Laure; Brunet, Philippe; Burtey, Stephane
Abstract: BACKGROUND AND AIMS: Chronic kidney disease (CKD) is considered as a public health problem. Almost 20%–25% of patients with end-stage kidney disease have been reported with an undetermined kidney disease (UKD) in large national registry. Recent data have shown that the number of monogenic disease-causing variants among patients with CKD is about 20%–30%. Monogenic disease-causing variants are underdiagnosed. We performed whole exome sequencing on patients in our centre with UKD. METHOD: All patients gave their written informed consent for genetic testing. Whole exome sequencing by next-generation sequencing was proposed in routine care practice to patient with UKD between January 2019 and December 2021. High and reproducible coverage achieved by our sequencing approach enabled copy-number variation (CNV) analysis. All patients with inconclusive biopsy results were included. Only one patient from the same pedigree was included. We excluded patients with a typical presentation of ADPKD, familial IgA nephropathy, patients with typical presentation of Gitelman or Bartter syndrome or established genetic diagnosis in the family. RESULTS: A total of 211 adult patients were included (120 males) with a median age of 48 years (range 37–62 years). Of these, 50 patients were treated with haemodialysis, 34 patients had a kidney transplantation. A total of 156 had self-declared Caucasian. Consanguinity was reported by 12 patients and suspected in 11 patients. Family history of kidney disease was present in 108 patients with both first and second degree affected in 38 patients. Kidney biopsy were inconclusive in 62 patients. Kidney biopsy was impossible in 57 incidents patients with CKD during the study period. A WES was performed first to avoid kidney biopsy in nine patients. A negative genetic testing prior to the WES with gene panel has been performed in 31 patients. We detected 27 monogenic renal disorders in 73 patients with either pathogenic or likely pathogenic variants and 5 copy number variants among 211 patients (37%). The glomerular disease represent the first yielded diagnostic subgroup in which Alport diseases (COL4A3/4/5) represent the dominant diagnostic (COL4A4 n  = 18; COL4A3 n  = 12; COL4A5 n  = 7; TTC21B n  = 3; APOL1 = 2; INF2 n  = 2; PAX2 n  = 2; TRPC6 n  = 2; TREX1 n  = 1; COQ8B n  = 1; NPHS1 n  = 1). Tubulointerstitial diseases is the second yielded diagnostic subgroup (UMOD n  = 7; NPHP1 n  = 2; NPHP3 n  = 1; CCL5 n  = 1; HNF1B n  = 1; CNM4 n  = 1; KCNJ1 n  = 1). Cystic disease and CAKUT is the third yielded diagnostic subgroup (PKHD1 n  = 3; DNAJB11 n  = 2; VHL n  = 1; PKD1 n  = 1; GREB1L n  = 1; PBX1 n  = 1). In addition, we find two patients with pathogenic complement variation (CFH et C3), one patient with TTR amyloidosis and one patient with familial renal glucosuria (SLC5A2). Six of the nine patients with WES first to avoid renal biopsy, have positive diagnostic (five Alport disease and one APOL1 nephropathy). Interestingly, one of these nine patients had a WES for nephrotic syndrome during type-I diabetes and a dialysis sister with undetermined glomerular disease and consanguineous parents, which detected a known variation in TTC21B gene (P209L) at a heterozygote state that did not explain the nephrotic syndrome. We performed Sanger sequencing for her sister and revealed the same variation at a homozygous state and explain her renal phenotype. Among 57 patients with impossible kidney biopsy, the WES was positive for 18 patients. The diagnostic yield of WES was higher in consanguineous patients (P = 0.04) and familial history of kidney disease (P < 0.0001). The diagnostic yielded reach 60.5% when the patient had family history of renal disease in both first and second degree of the pedigree. CONCLUSION: WES identified a molecular diagnosis in almost 40% of patients with UKD in our centre. An exome first may have a high diagnostic yielded and avoid an invasive procedure like kidney biopsy or when it is impossible. WES must be included as a standard of care for patients with UKD.